The Role of Peanuts: Nutritional, Bioactive, Food Technology and Novel - Sutrisno Adi Prayitno; Khoiroh Inda Dini; Natasya Zahra Aulia Putri; Muh. Sulaiman Dadiono (Academic Letters, 2025)
Peanuts (Arachis hypogaea L.) are globally significant legumes that play an important role in food technology, human nutrition, and sustainable agriculture. As the fourth most important oilseed crop worldwide, peanuts contribute substantially to global food security, particularly as an affordable source of plant-based protein and energy. This review highlights the nutritional composition of peanuts, emphasizing their high content of proteins, unsaturated fatty acids, dietary fiber, essential vitamins, minerals, and diverse bioactive compounds such as polyphenols, phytosterols, and resveratrol. These components support cardiovascular health, metabolic regulation, and the prevention of chronic degenerative diseases. The paper also discusses the growing utilization of peanuts and their by-products in food technology, including the development of functional foods, protein-rich ingredients, and nutraceuticals through innovative and sustainable processing technologies. Furthermore, the valorization of peanut by-products aligns with circular economy principles by reducing waste and enhancing resource efficiency. Overall, peanuts represent a multifunctional food crop with significant potential to improve nutrition, public health, and sustainable food systems.